Structural, optical and antibacterial properties of zinc oxide nanoparticles synthesized via chemical and green synthesis methods - Ribut, Siti Huzaimah (2019)
Zinc oxide nanoparticles (ZnONPs) are subjected to intense research due to their wide application in various fields such as electronics, solar cells and optics, and another impressive property. In terms of biological application, in wastewater treatment, chemical disinfection like chlorination can respond with various components in natural water yielding to the by-product formation that possibly hazardous to the environment which could harmfully affect human health. Metal oxide nanoparticles can be one of the options to enhance the wastewater treatment since it is partly neutral to water and not a strong oxidant. To reduce the use of harmful chemicals and by-product formation in wastewater treatment, the use of plant extract in the synthesis of nanoparticles are cost-effective and environmentally friendly. Therefore, the ZnONPs and biogenic ZnONPs was successfully synthesized using chemical and green synthesis method. The structural, optical and the antibacterial properties of both ZnONPs and biogenic ZnONPs was revealed by characterization and antibacterial activity against Escherichia coli bacteria. For structural properties, XRD test showed that both ZnONPs and biogenic ZnONPs have a wurtzite structure as the peaks of zinc oxide (ZnO) dominated in (002) plane. Then, the FESEM result revealed that the ZnO formed in a spherical shape and the nanoparticles sizes measured is a range around 60 ± 12 nm - 24 ± 4 nm for both ZnONPs and biogenic ZnONPs. For optical properties, the energy band gap obtained is between 3.33 – 3.37 eV. For ZnONPs synthesis by chemical method, the antibacterial test discovered that ZnONPs prepared at pH 10 & 11 shows the significant inhibition compared to other pH values. Meanwhile, the biogenic ZnONPs at 0.1 M concentration exhibit the highest inhibition of E. coli bacteria due to their smallest size of nanoparticles. The results obtained indicated that both ZnONPs and biogenic ZnONPs exhibit the significant inhibition towards bacteria growth due to their great properties in structural and optical.